THE PROPOSED REFORM OF THE EUROPEAN EXTERNAL ACTION SERVICE AND ITS IMPLICATIONS FOR THE EUROPEAN UNION'S SECURITY POLICY (Journal of the Spanish Institute for Strategic Studies, 2018)
The aim of this article is the analysis of the European External Actions Service’s shortfalls, to determine whether these are structural or circumstantial, the assessment of the draft reform submitted by the European Union High Representative for Foreign Affairs and Security Policy and the proposal, where relevant, of reform guidelines to improve this policy, also under review, and in particular in accordance with the conclusions of the European Council in December 2013.